Detection of brucellosis and leptospirosis in feral pigs in New South Wales. Issue 9 (23rd June 2014) - Ridoutt, C; Lee, A; Moloney, B; Massey, PD; Charman, N; Jordan, D
<x xml:space="preserve">Abstract</x> Objective To determine the presence and estimate the prevalence of Brucella suis, Leptospira interrogans serovar Pomona (hereafter L. pomona) and Leptospira borgpetersenii serovar Hardjo (hereafter L. hardjo) in feral pigs culled in New South Wales (NSW), Australia. Methods During 2012 and 2013, 239 serum samples were collected from feral pigs killed as pests or game in NSW. All sera were subjected to the rose‐bengal test for B. suis, with positives subjected to the complement fixation test (CFT). Attempts were made to detect B. suis by culture and PCR on CFT‐positive samples. All sera were tested separately for the presence of L. pomona and L. hardjo antibodies using the microscopic agglutination test. Results Of 238 samples tested, 7 were positive (4 with CFT titres ≥ 32) for B. suis antibodies (3% seroprevalence). However, B. suis was not cultured or detected by PCR. Of 239 sera tested for L. pomona antibodies, 126 samples were positive (53%) and 9 (4%) were positive for L. hardjo. Conclusions The findings are the first tangible evidence that feral pigs in northern NSW harbour B. suis, providing a plausible explanation for recent human and canine cases of brucellosis related to pig hunting. The increased seroprevalence of L. pomona occurred in years preceded by flooding and rodent plagues, suggesting a potential for zoonotic infection much greater than previously realised. Advice to the community should focus on encouraging the adoption of improved hygiene practices during pig hunting and consideration of vaccinating livestock against leptospirosis.